A rare blood group found in Bangladeshi population - Dipta, Tashmim Farhana; Islam, Asadul (Bangladesh Journal of Pathology, 2010)
Key words: Bombay blood group; O blood group DOI: 10.3329/bjpath.v25i1.4129 Bangladesh J Pathol 25(1): 25-27